MENINGKATKAN EFISIENSI PENGELOLAAN ARSIP KEPEGAWAIAN DI KABUPATEN BADUNG MELALUI PENGEMBANGAN SISTEM INFORMASI MANAJEMEN ARSIP DIGITAL - Ida Ayu Tri Sabina Putri; I Wayan Supriana; Putu Praba Santika (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The issues faced by the community, particularly government employees in Badung Regency, regarding the efficiency of personnel records management, served as the foundation for the development of the Personnel Records Management Information System. The scope of the activity includes the development of a web-based system to replace the manual process of storing employee records, which has been prone to damage and data loss. The methods used involved preparation stages, system development, user training, and technical assistance for staff. The results show that the system improves access speed and facilitates more organized personnel archiving. This activity demonstrated that the Personnel Records Management Information System is effective in enhancing public service quality and meeting the needs of administrative digitalization in government. The sustainability of the program is supported by collaboration with the Badung Regency Agency for Personnel and Human Resources Development (BKPSDM), and is expected to have a long-term positive impact.